Application of Elements of Article 112 Paragraph (1) of Law Number 35 of 2009 concerning Narcotics - Leba Max Nandoko Rohi; Tanudjaja (Dinasti Research, 2025)
Narcotics crimes often involve economically unstable individuals who store or distribute drugs as a shortcut to profit. The Ridho Fahmi Nurlete case (Number 108/PID.SUS/2024/PT AMB) shows ambiguity in the application of Article 112 paragraph (1) of Law Number 35 of 2009, which creates uncertainty in proving drug possession and is often considered unfair in distinguishing the role of users or dealers. This study aims to analyze the elements of the crime and the judge's consideration in the verdict. This type of research is legal research. By using the method of Legislative Approach and case approach. And analyzed using juridical qualitative. The results of the study state that the elements of Article 112 paragraph (1) of the Narcotics Law have been fulfilled in the Ridho Fahmi Nurlete case. The element of “every person” was proven through the presence of the defendant, and the element of “without the right to possess narcotics Group I” was proven by the evidence of synthetic narcotics. The judge considered the defendant as a user, not a dealer, because the evidence was less than 1 gram, in accordance with Supreme Court Circular Letter No. 1 of 2017. The sentence of 1 year and 6 months was upheld, with consideration of the defendant's minor role and the applicable legal provisions.